To solve the equation \( 3 - 2x + 1 \cdot 3 - 2x - 3 = 3 - 3 \), we first simplify the equation.
We start by rewriting it clearly:
\[ 3 - 2x + 1 \cdot 3 - 2x - 3 = 3 - 3 \]
The left-hand side simplifies to:
\[ 3 - 2x + 3 - 2x - 3 = 3 - 3 \]
Combine like terms:
\[ (3 - 3) + (-2x - 2x) = 0 \]
This gives us:
\[ -4x = 0 \]
Now, divide both sides by -4:
\[ x = 0 \]
Let's check our options:
- \( x = \frac{14}{1} \)
- \( x = -\frac{2}{3} \)
- \( x = -2 \)
- \( x = -4 \)
- \( x = \frac{-5 \pm \sqrt{73}}{8} \)
None of these options show \( x = 0 \). Therefore, either there was an error in the equation transcription or they are incorrect options.
If you could double-check the original equation or provide more context, that might help clarify the situation.